Antibiotic sensitivity patterns of uropathogens in hospitalized patients at Teaching Hospital Jaffna - Thilukshikka, K.; Anuruddha, A.N.; Spelman Croos, M.V.; Erandi, R.; Pravina, S.; Kumar, R.; Balagobi, B.; Rajanthi, R.; Ambalavanar, V. (The Jaffna Medical Association, 2024)
Indiscriminate use of antibiotics has led to the emergenceof antibiotic resistance in hospital settings. Awareness of local antimicrobial resistance patterns is essential forprudent empirical therapy of urinary tract infections.This study describes the uropathogens isolated, their antibiotic sensitivity patterns and associated factors inadult inpatientswith a positive urine culture at Teaching Hospital Jaffna. All positive urine culture reports and relevant request forms of adult inpatients (≥18years) investigated at the Microbiological Unit of Teaching Hospital Jaffna during a three-month period (October 1st to December 31st 2020) were analyzed retrospectively with SPSS v27. Standard descriptive statistics and the chi square test were used (critical value 0.05). Data were extracted from 426 culture reports. Mean age of the sample was 53.2 years (SD 19.9); 47.2% (n=201) of the reports belonged to patients ≥60 years and 60.1% (n=256) were of females. Antibiotics prescribed prior to culture were documented in 183 (43%) reports. The most commonly prescribed empirical antibiotic was co-amoxiclav (24%, n=183). Coliforms were the commonest isolate (63.4%, n=270) and showed resistance to several commonly prescribed antibiotics; antibiotic sensitivity was relatively low to ampicillin (9.5%), ceftriaxone (40%) and amoxicillin (48.1%); highest susceptibility was to meropenem (87.6%). Age group and gender were significantly associated with the type of uropathogen isolated (p≤0.05). Prior antibiotic therapy was common among inpatients now with urinary tract infection at the Teaching Hospital Jaffna. Sensitivity patterns suggest that antibiotic resistance is a major concern. Empirical therapy needs to be guided by institutional policies and local sensitivity patterns.
Keywords: Uropathogens; Urinary tract infection; Antimicrobial resistance; Antibiotic therapy; Coliforms